PERBEDAAN MAKNA HIDUP LANSIA YANG TINGGAL DI PANTI WERDHA SENJA CERAH DAN YANG TINGGAL BERSAMA KELUARGA DI DESA - Baris, Alicia Benaya Wasti; Bidjuni, Hendro; Rompas, Sefti (Universitas Sam Ratulangi, 2019)
Abstrack: The meaning of life is something that is considered very important and valuable, and provides special value for someone and deserves to be a goal in life. Being someone who means and feels valuable in life seems very important when entering the elderly period. At this time, the elderly must be able to accept, be positive and be able to live their old age in peace. The aim is to find out the difference in the meaningoflife of the lives of the elderly who live in nursing home senja cerah and Who Live with Family in Sea Satu Village Pineleng District. The research design used is Observational Analytic with Cross Sectional Study approach. A sample of 30 respondents was obtained using the Purposive Sampling technique. The results of statistical test studies using the T-test at a significance level of 95%, obtained a significant value Ï = 0.008 <Î± (0.05). The conclusion is that there is a difference in the meaningoflife of the lives of the elderly who live in nursing home senja cerah and who live with their families.Keywords : Elderly, Meaning of LifeAbstrak : Makna hidup adalah sesuatu yang dianggap sangat penting dan berharga, serta memberikan nilai khusus bagi seseorang dan layak dijadikan tujuan dalam kehidupan. Menjadi seseorang yang berarti dan merasa berharga dalam hidup tampaknya sangat penting saat memasuki periode lansia. Pada masa ini, lansia harus dapat menerima, bersikap positif serta dapat menjalani masa tuanya dengan tenang Tujuan untuk mengetahui perbedaan makna hidup lansia yang tinggal di panti werdha senja cerah dan yang tinggal bersama keluarga di desa sea satu kecamatan pineleng. Desain penelitian yang digunakan yaitu Observasional Analitik dengan pendekatan Cross Sectional Study. Sampel berjumlah 30 responden yang didapat dengan menggunakan tehnik Purposive Sampling. Hasil penelitian uji statistik menggunakan uji T-test pada tingkat kemaknaan 95%, didapatkan nilai signifikan Ï = 0,008 < Î± (0,05). Kesimpulan ada perbedaan makna hidup lansia yang tinggal di panti werdha senja cerah dan yang tinggal bersama keluarga.Kata kunci : Lansia, Makna Hidup